2021
DOI: 10.1071/cp20245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of disease severity caused by four soil-borne pathogens in winter cereal seedlings

Abstract: In Australia, crown rot of cereals is predominantly caused by Fusarium pseudograminearum and Fusarium culmorum, and common root rot by Bipolaris sorokiniana. Fusarium graminearum is an important pathogen causing Fusarium head blight worldwide and has also been reported to cause crown rot of wheat. The comparative ability of F. pseudograminearum, F. culmorum, F. graminearum and B. sorokiniana to cause crown rot and common root rot across a range of winter cereal species requires investigation. In glasshouse tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
3
15
1
Order By: Relevance
“…pseudograminearum, and F. moniliforme could lead to wheat root rot disease. Inhibitory activities of 18f against these fungi were also evaluated (Figure ), and EC 50 values were calculated (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pseudograminearum, and F. moniliforme could lead to wheat root rot disease. Inhibitory activities of 18f against these fungi were also evaluated (Figure ), and EC 50 values were calculated (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Activities of 18f against Different Fusarium Pathogens. Fusarium pathogens including F. graminearum, F. culmorum, F. pseudograminearum, and F. moniliforme 41 could lead to wheat root rot disease. Inhibitory activities of 18f against these fungi were also evaluated (Figure 5), and EC 50 values were calculated (Table 3).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Physiological (relative water content, membrane stability index, and chlorophyll content) and non-enzymatic metabolites (soluble sugar, protein, soluble phenol, and flavonoid content) parameters of cereal plants inoculated with B. sorokiniana 191 are changed (Satti et al, 2021;Holz et al, 2022). Leaf sheaths and subroot internodes of barley and winter wheat seedlings can be affected by root rot by 64.7-99.6% (Saad et al, 2021). According to our data, 42-53% of winter wheat plants were healthy, 32-41% were slightly affected by common root rot disease and 10-21% were moderate to severely affected.…”
Section: Discussionmentioning
confidence: 99%
“…The disease can manifest itself as browning, yellowing, and mildew in young leaves (Rysbekova and Sultanova, 2022). Saad et al (2021) evaluated the ability of F. pseudograminearum, F. culmorum, F. graminearum, and B. sorokiniana to cause root rot in winter cereals. It was found that barley and soft wheat plants had the highest rates of disease development on leaf sheaths and root internodes (64.7-99.6%), while these indexes were low on oats (5%).…”
Section: Discussionmentioning
confidence: 99%